Mosaic isochromosome 20q at amniocentesis: Prenatal diagnosis, genetic counseling and literature review - Chih-Ping Chen; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Dai-Dyi Town; Wayseen Wang (Elsevier, 2019)
Objective: We present prenatal diagnosis of mosaic isochromosome 20q [i(20q)] at amniocentesis, and we review the literature. Case report: A 36-year-old woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 46,XY,i(20)(q10)[27]/46,XY[29]. Prenatal ultrasound findings were unremarkable. The parental karyotypes were normal. Repeat amniocentesis was performed at 20 weeks of gestation. During repeat amniocentesis, array comparative genomic hybridization (aCGH), interphase fluorescence in situ hybridization (FISH) and quantitative fluorescent polymerase chain reaction (QF-PCR) assay were performed on uncultured amniocytes, and conventional cytogenetic analysis, interphase FISH and aCGH were performed on cultured amniocytes. In the repeat amniocentesis, the cultured amniocytes revealed a karyotype of 46,XY. Interphase FISH analysis showed the i(20q) signal in 5.2% (5/96) of the uncultured amniocytes compared with 2% in the control, and in 0.98% (1/102) of the cultured amniocytes compared with 2% in the control. aCGH detected no genomic imbalance in both uncultured and cultured amniocytes. QF-PCR analysis excluded uniparental disomy 20. At 38 weeks of gestation, a healthy 2870-g male baby was delivered with no phenotypic abnormality. The postnatal blood karyotype was 46,XY. FISH analysis on urinary cells showed 2.1% (2/95 cells) mosaicism compared with 1.9% (2/105 cells) in the control. Conclusion: Mosaic i(20q) at amniocentesis is a benign condition associated with a favorable outcome in most cases and can be a cell culture artifact confined to cultured amniocytes. Molecular cytogenetic analysis using uncultured amniocytes is useful for rapid confirmation. Prenatal diagnosis of very high percentage of mosaicism for i(20q) at amniocentesis should alert the presence of fetal structural abnormalities. Prenatal diagnosis of mosaic i(20q) at amniocentesis should include a detail examination of fetal brain and spine. Keywords: Amniocentesis, Amniocytes, Isochromosome 20q, Mosaicism, Prenatal diagnosis